Blood or Crystalloids for Hemorrhagic Shock—Response to the Agency for Healthcare Research and Quality - Julia R. Coleman; Reynold Henry; Nakul Raykar; John B. Holcomb (JAMA Surgery, 2026)
This Viewpoint evaluates the Agency for Healthcare Research and Quality report on prehospital blood transfusion and fluid interventions for hemorrhagic shock and argues that its claims of scientific equipoise stem from methodologic challenges instead of clinical equivalence of blood transfusion and crystalloid therapy.